PENGEMBANGAN PHYSICS PARAMETER MONITORING SYSTEM (PPMS) BERBASIS IOT UNTUK PEMBELAJARAN MENGANALISIS CUACA - Nanda Luspita; Yudi Guntara; Ganesha Antarnusa (Charm Sains: Jurnal Pendidikan Fisika, 2025)
This study aims to determine the characteristics and feasibility of Physics Parameter Monitoring System (PPMs) media on Temperature Heat material to analyze the weather. The research method used is Research and Development (R&D) with the 4-D development model. The stages of the 4-D model consist of 4 stages, namely the define stage, design stage, develop stage, and disseminate stage. The subjects of this study consisted of an expert validation and a limited trial to 20 students who had not learned the material of Heat Temperature. The results of expert validation of teaching aids obtained a score of 87%. The results of expert validation of LKPD obtained a value of 82%. The assessment results from students as users amounted to 83.6%. The PPMs media on temperature and heat material that has been developed shows its suitability for use in learning.